Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition. (5th November 2017) - Yao, You-Li; Han, Xin; Song, Jian; Zhang, Jing; Li, Ya-Mei; Lian, Li-Hua; Wu, Yan-Ling; Nan, Ji-Xing
Graphical abstract: Highlights: Acanthoic acid protects against ethanol-induced liver injury. AA recruited LKB1-AMPK phosphorylation and activated SIRT1 to regulate alcoholic liver injury. AA inhibited IRAK1/4 signaling pathway against chronic alcohol consumption. Abstract: The aim of this study was to investigate the effects of acanthoic acid (AA) on the regulation of inflammatory response, lipid accumulation, and fibrosis via AMPK- IRAK4 signaling against chronic alcohol consumption in mice. Ethanol-induced liver injury was induced in male mice by Lieber-DeCarli diet for 28 d. And mice in AA groups were gavaged with AA (20 or 40 mg/kg) for 28 d. AA treatment significantly decreased serum AST and TG, hepatic TG levels, serum ethanol and LPS levels compared with chronic ethanol administration. AA ameliorated histological changes, lipid droplets, hepatic fibrosis, and inflammation induced by ethanol. AA significantly increased the expressions of p-LKB1, p-AMPK, and SIRT1 caused by chronic ethanol administration, and attenuated the increasing protein expressions of IRAK1 and IRAK4.siRNA against AMPKα1 blocked AMPKα1 and increased IRAK4 protein expressions, compared with control-siRNA-transfected group, while AA treatment significantly decreased IRAK4 expressions compared with AMPKα1-siRNA-transfected group. AMPK-siRNA also blocked the decreased effect of AA on inflammatory factors. AA decreased over-expression of IRAK4 and inflammation under ethanol plus LPS challenge. AA recruited LKB1-AMPK phosphorylation and activated SIRT1 to regulate alcoholic liver injury, especially, inhibited IRAK1/4 signaling pathway to regulate lipid metabolism, hepatic fibrosis and inflammation caused by alcohol consumption.